Analysis of Land and Building Tax Accounting Supervision at the Asahan Regency Revenue Service - Zulia Hanum (Journal of International Conference Proceedings (JICP), 2021)
The purpose of this study was to determine whether the land and building tax accounting supervision carried out by the Asahan Regency Revenue Service was functioning effectively. To find out what causes the land and building tax target to be not achieved. This research approach uses a descriptive approach. The types of data used are quantitative and qualitative data. Sources of data used are primary and secondary data. Data collection techniques used are documentation techniques and interview techniques. The data analysis technique used is descriptive method. Based on the results of this study, it can be concluded that the supervision of land and building tax accounting with revenue targets in its implementation is less effective, resulting in the realization not reaching the targets set at the Asahan Regency Revenue Service.